2011
DOI: 10.1158/0008-5472.can-10-1375
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Chain Ferritin siRNA Delivered by Cationic Liposomes Increases Sensitivity of Cancer Cells to Chemotherapeutic Agents

Abstract: Approximately half of all gliomas are resistant to chemotherapy, and new therapeutic strategies are urgently needed to treat this cancer. We hypothesized that disrupting iron homeostasis in glioma cells could block tumor growth, based on an acute requirement for high levels of iron to meet energy requirements associated with their rapid growth. Ferritin is best known as an intracellular iron storage protein, but it also localizes to tumor cell nuclei where it seems to protect DNA from oxidative damage and to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 31 publications
(36 reference statements)
4
52
0
1
Order By: Relevance
“…In order to apply this knowledge to cancer biology and tumor growth we developed a nanotechnology platform to produce an acute decrease in ferritin expression. Using this approach we previously demonstrated that a significant but transient change in iron homeostasis in cancer cells following exposure to ferritin siRNA is coupled with an increased sensitivity to chemotherapeutic agent [1] and we expand this finding in the present study to radiosensitivity in both in vitro and in vivo models. The results of this study demonstrate that reducing expression of H-ferritin in human glioblastoma cells disrupts iron homeostasis, promotes oxidative stress, alters DNA repair mechanisms, and increases cell sensitivity to radiation.…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…In order to apply this knowledge to cancer biology and tumor growth we developed a nanotechnology platform to produce an acute decrease in ferritin expression. Using this approach we previously demonstrated that a significant but transient change in iron homeostasis in cancer cells following exposure to ferritin siRNA is coupled with an increased sensitivity to chemotherapeutic agent [1] and we expand this finding in the present study to radiosensitivity in both in vitro and in vivo models. The results of this study demonstrate that reducing expression of H-ferritin in human glioblastoma cells disrupts iron homeostasis, promotes oxidative stress, alters DNA repair mechanisms, and increases cell sensitivity to radiation.…”
Section: Discussionsupporting
confidence: 56%
“…Nuclear ferritin is composed mainly of H-ferritin and is believed participate in the transcriptional regulation and DNA protection [42]. In our previous study, we found that H-ferritin is capable of protecting naked DNA in the presence of BCNU, a DNA alkylating chemotherapeutic agent [1]. In the current study we extend this idea to radiation (Figure 4).…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations